Efficient hydrogenation of levulinic acid in water using a supported Ni–Sn alloy on aluminium hydroxide catalysts. Issue 9 (16th December 2015) - Rodiansono; Astuti, Maria Dewi; Hara, Takayoshi; Ichikuni, Nobuyuki; Shimazu, Shogo
Abstract : Efficient hydrogenation of levulinic acid (LA) into γ-valerolactone (GVL) in water using supported Ni–Sn(1.4)/AlOH consisting of Ni3 Sn2 alloy species was achieved with high selectivity towards GVL and the catalyst could be reused without any significant loss of activity and selectivity. Abstract : Efficient hydrogenation of levulinic acid (LA) into γ-valerolactone (GVL) in water using highly dispersed Ni–Sn(x)/AlOH (x = Ni/Sn ratio) was studied. Increasing the Sn amount in the Ni–Sn alloy up to 2.14 mmol g −1 enhanced the yield of GVL, which slightly decreased when the Sn content was nearly 4 mmol g −1 (feeding Ni/Sn = 1.0). A stoichiometric amount of GVL (>99%) was achieved by using Ni–Sn(x)/AlOH (x = 3.0 and 1.4) at 393 K for 120 min in H2 O. H2 -treated Ni–Sn(1.4)/AlOH consisting of Ni3 Sn2 alloy species showed high selectivity towards GVL (>99% yield). The Ni–Sn(1.4)/AlOH catalyst was reusable for at least six consecutive runs without any significant loss of activity and selectivity.